Analysis and wave tank verification of the performance of point absorber WECs with different configurations. Issue 14 (1st August 2021) - Li, Xiaofan; Martin, Dillon; Jiang, Boxi; Chen, Shuo; Thiagarajan, Krish; Parker, Robert G.; Zuo, Lei
Abstract: Extracting energy from ocean waves has become a heated topic since the energy crisis of the 2000s. Among all the different concepts and designs of Wave Energy Converter (WEC), point absorber is a widely adopted type with great potential, and various configurations and constraints are applicable to it. Here, the point absorber WECs with four different set‐up configurations are explored: single body heaving WEC, two‐body heaving WEC, two‐body WEC with a flat plate (Reference Model 3), and a two‐body WEC with a cylinder‐shaped second body. Dynamic models are established for each case and wave tank tests are conducted for verification. The results show that the power capture of a point absorber can benefit from several aspects: the two‐body WEC with a streamlined shape can double the wave capture width ratio (up to 66.5%) over the single‐body WEC or Reference Model 3, while coupling other motion or mooring dynamics can further improve the capture width ratio by 12% by increasing the relative motion stroke.